Audience Perspectives on Paying for Local News: A Regional Qualitative Case Study. (11th June 2021) - Ross, Angela; Lester, Libby; Konkes, Claire
ABSTRACT: Local and regional journalism is perceived to aid the functioning of democracy. Yet local publications are increasingly being forced to close due to the collapse of pre-digital news business models. An emerging area of scholarship considers potential funding solutions for local news media. One key enquiry is how local news publishers may attract more revenue from their audiences. This is a difficult task for all news organisations, yet even more so for local news publishers due to evidence news consumers are less willing to pay for local news than other types. This paper contributes by developing a deeper conceptual understanding of factors contributing to people being unwilling to pay for local news. We use data from a 2019 3-month digital ethnographic regional Australian case study to identify several structural and relational factors that contributed to participants being unwilling to subscribe to their local publication. We consider how these findings may be used by local news publishers to maintain and increase their subscription base.